Efficacy and safety of primary thromboprophylaxis for the prevention of venous thromboembolism in patients with cancer and a central venous catheter: A systematic review and meta-analysis. Issue 208 (December 2021) - Li, Allen; Brandt, Willem; Brown, Cameron; Wang, Tzu-Fei; Ikesaka, Rick; Delluc, Aurélien; Wells, Phil; Carrier, Marc
Abstract: Background: Venous thromboembolism (VTE) is a leading cause of mortality in patients with cancer and is associated with significant morbidity and healthcare expenditure. The risk of VTE is increased following the insertion of a central venous catheter (CVC) for chemotherapy delivery and supportive care. The risks and benefits of primary thromboprophylaxis in patients with cancer and CVC are unclear. Objective: We sought to assess the rates of VTE and bleeding complications and to determine the efficacy and safety of primary thromboprophylaxis in adult patients with cancer and a CVC. Methods: A systematic search of MEDLINE, EMBASE, and all EBM was conducted. Randomized controlled trials (RCTs) of adult patients with cancer and a CVC receiving primary thromboprophylaxis compared to observation/placebo were included. The primary efficacy and safety outcomes were total VTE and major bleeding episodes, respectively. Results: A total of 12 RCTs (3545 patients) were included in the analysis. The total rates of VTE were significantly lower in patients receiving thromboprophylaxis compared to those not receiving primary prevention (7.6% vs. 13%; Odds Ratio (OR) 0.51, 95% CI 0.32–0.82, p  < 0.01). The rates of major bleeding complications were not higher in patients receiving thromboprophylaxis (0.9% vs. 0.6%; OR 1.12, 95% CI 0.29–4.40, p  = 0.87). Conclusions: Primary thromboprophylaxis significantly reduced the risk of VTE without increasing the risk of major bleeding complications in patients with cancer and CVC. Future studies are needed to confirm these findings. Highlights: Venous thromboembolism (VTE) is common in patients with cancer and a central venous catheters (CVC). The efficacy and safety of primary thromboprophylaxis are unknown in patients with cancer and CVC. The total rates of VTE were significantly lower in patients receiving thromboprophylaxis. There were no differences in major bleedings between patients receiving thromboprophylaxis or not.